2010
DOI: 10.18438/b81w4j
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Acquisition of Electronic Medical Texts on the Usage of Equivalent Print Books in an Academic Medical Library

Abstract: the terms of the Creative CommonsAttribution-Noncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/by-ncsa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjectives -This study examines whether acquiring a text in electronic format effects the usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Our respondents' preferred information sources used to meet information needs related to medications, treatments, and continuing professional development are consistent with reports in literature [1,2,4,7,8], namely electronic resources and (other) colleagues. Time and poor search skills were stated key barriers to accessing web-available health information.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our respondents' preferred information sources used to meet information needs related to medications, treatments, and continuing professional development are consistent with reports in literature [1,2,4,7,8], namely electronic resources and (other) colleagues. Time and poor search skills were stated key barriers to accessing web-available health information.…”
Section: Discussionsupporting
confidence: 84%
“…These point-of-care tools are an efficient vehicle for learner education and continuing professional development, especially in an era of information saturation and evidence-based medicine. With the decrease in physical accessing of libraries that online resources have helped cultivate, web-based and point-of-care tools ("toolkits") may facilitate an information push approach that promotes information discovery by the end-user [4,5].…”
Section: Informatics Faculty Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As the use of smart phones, desktops and handheld computers becomes more prevalent, library users are making use of increasingly flexible access to medical information. Health libraries commonly report that loans of printed material are declining, whilst subscriptions to, and use of, electronic books and journals are increasing . Additionally, an ever‐growing number of NHS organisations have started to subscribe to online evidence‐based products, at a cost of several thousand pounds per institution per year.…”
Section: Introductionmentioning
confidence: 99%
“…Only 5 years later, a comparative usage of science e-book and print collections at Texas A&M University libraries demonstrated that e-books were used over 10 times more than the print books in science and chemistry and more than 200 times that of their print counterparts in computer science (6). Memorial University of Newfoundland's study also reported substantially more usage was being made of electronic books than print books (7). These studies showed that when surveyed, library users said they preferred print.…”
Section: Introductionmentioning
confidence: 99%